Tree of ethos a vertical disposition in the heart of the CBD - Hayes, Ruan (My University, 2018)
This thesis symbolises the notion of the tree as an interpretive device for a new methodology of the skyscraper - a typology which is able to dictate the balance between order and disorder and to serve as protection from and resourcing of the future demands of the City. The spirit of the tree contests the ethos of a fractured City and relates to the characteristic spirit of the diverse cultures of the city. It conveys an era of unity for the diverse cultures living, working and playing in the City, expressed as an initial iteration of an inclusive vertical city within a city, manifested in the attitude and aspirations of a growing Johannesburg. This research report centers on Johannesburg’s current and future demands in terms of the notion of urban life within the building structuring policies of the City. It endevours to explore theories of inclusive urban ordering systems with specific focus on the skyscraper as an iteration within the dense grid confined by physical barriers of separation. The author’s research analyzes the factors keeping Johannesburg attached to the legacy of segregation embedded in the spatial order - regulatory barriers and infrastructure dictated through a fragmented skyline. The research further challenges those principles for a unique and inclusive urban life which starts at enclaves of current and future skyscrapers. By analysing the demands of future urban conditions such as rapid urbanisation and climate change, an initial statement can be visualised into a response for a resilient future City model. Through a clear understanding of the factors which have shaped the skyline and which still dictate the fragmented urban life within the City, it is hoped that this proposal will introduce a new inclusive order as an initial vertical iteration within the heart of the CBD.